2003
DOI: 10.1023/b:jecr.0000015667.26510.09
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Firing Conditions Grain Boundary Structure and Magnetic Properties in Polycrystalline MnZn-Ferrites

Abstract: Abstract. The influence of the firing conditions on the nanoscale structure of the grain boundaries and on the magnetic properties of polycrystalline MnZn-ferrites is investigated, on specimens of nearly identical microstructures. High oxygen partial pressures favor accumulation of impurity ions at the triple points. Under appropriate oxygen pressures homogeneous accumulation of impurities along the grain boundaries may occur, revealing therefore chemically pure grains and low hysteresis losses; simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The effect of the oxygen partial pressure on the grain boundary structure of MnZn-ferrites in the absence of titanium has been discussed earlier [17]. Although the partial pressure of oxygen is the only cation vacancy generating mechanism for morphologically identical microstructures, adjusting the occupancy of the peak temperature during the sintering cycle brings the results in qualitative agreement with this study.…”
Section: Discussionsupporting
confidence: 86%
“…The effect of the oxygen partial pressure on the grain boundary structure of MnZn-ferrites in the absence of titanium has been discussed earlier [17]. Although the partial pressure of oxygen is the only cation vacancy generating mechanism for morphologically identical microstructures, adjusting the occupancy of the peak temperature during the sintering cycle brings the results in qualitative agreement with this study.…”
Section: Discussionsupporting
confidence: 86%
“…It is observed that, increasing O 2 content, the high temperature losses is lower. The present results confirm Lebourgeois et al [12], which mention, as Zaspalis [6,7], Eq (1). According to Eq.…”
Section: Resultssupporting
confidence: 93%
“…Existence of Fe +2 implies in free electrons inside the lattice, thus increasing the conductivity. Morineau and Paulus [5] and Zaspalis et al [6,7] point out that the amount of Fe +2 may be controlled with oxygen pressure. Increasing oxygen, the amount of Fe +2 is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Desired physical properties could then be considered in the setup of the manufacturing process. Such a material development approach could make use of existing literature on the link between manufacturing conditions and material properties [14], [15], [26].…”
Section: Discussionmentioning
confidence: 99%